PERAN GURU DALAM MENGINTEGRASIKAN NILAI KEBERAGAMAN MELALUI KEGIATAN EKSTRAKURIKULER DI SEKOLAH DASAR - Nur Khosiah (PT Innovative Academic Journals, 2025)
Basic education has an important role in instilling the values ​​of cultural diversity in students through various means, one of which is extracurricular activities. This research aims to analyze teacher practices in teaching cultural diversity through extracurricular activities at MI Tarbiyatus Sibyan, Lumbang, Probolinggo. This research uses a qualitative approach with a case study method. Data was collected through observation, in-depth interviews with teachers, and documentation of extracurricular activities at MI Tarbiyatus Sibyan which has a multicultural student background. The research results show that teacher practice in teaching cultural diversity involves a creative approach through scout extracurriculars, traditional games, and group discussions. With proper implementation, extracurricular activities can be an effective means of instilling the value of cultural diversity in elementary school students, supporting the creation of a healthy society. tolerant and harmonious in the future.